2020
DOI: 10.1021/acs.est.9b06484
|View full text |Cite
|
Sign up to set email alerts
|

Energy System Pathways with Low Environmental Impacts and Limited Costs: Minimizing Climate Change Impacts Produces Environmental Cobenefits and Challenges in Toxicity and Metal Depletion Categories

Abstract: B. (2020). Energy system pathways with low environmental impacts and limited costs: minimizing climate change impacts produces environmental cobenefits and challenges in toxicity and metal depletion categories. Environmental Science and Technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…For example, the expansion and operation of technologies in the heat and transport sectors are not included. Vandepaer et al [18] used a multi-sectoral ESOM for Switzerland and showed, for instance, that in an energy system optimized towards life cycle GHG emissions, additional power generation capacity is added to deploy a higher proportion of hydrogen-based transportation technologies compared to the cost-optimal solution where transportation is mostly based on battery electric vehicles. Therefore, the sectoral extension of the approach presented in our study is crucial to fully understand the impact of considering life cycle GHG emissions on the structure and overall environmental performance of the entire energy system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the expansion and operation of technologies in the heat and transport sectors are not included. Vandepaer et al [18] used a multi-sectoral ESOM for Switzerland and showed, for instance, that in an energy system optimized towards life cycle GHG emissions, additional power generation capacity is added to deploy a higher proportion of hydrogen-based transportation technologies compared to the cost-optimal solution where transportation is mostly based on battery electric vehicles. Therefore, the sectoral extension of the approach presented in our study is crucial to fully understand the impact of considering life cycle GHG emissions on the structure and overall environmental performance of the entire energy system.…”
Section: Discussionmentioning
confidence: 99%
“…The information considered in the ESOM for the adjustment of the LCA indicators is efficiency and lifetime to ensure consistency and to allow for the correct consideration of the impacts from construction (see Equations (2) and 3), in line with earlier integration work [16,18].…”
Section: Life Cycle Indicatorsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, such adaptions of the background database are difficult to operationalise with the current software tools. Thus matrix-based approaches, such as those presented in Mendoza Beltran et al [42], Vandepaer et al [43] or Fernández Astudillo et al [6], are becoming increasingly relevant, which also meet the transparency criteria proclaimed by parts of the research community [44,45].…”
Section: Methodsological Limitationsmentioning
confidence: 99%
“…Only a few studies have focused on integrating LCA indicators to ESMs [18][19][20][21]. However, these studies either follow the ex-post assessment approach [18,19], or aggregate all considered environmental impacts into only one or a few indicators [20,21], though a multi-objective optimization approach is applied. None of them has thoroughly analyzed the potential impacts on the shape of the electricity system if the trade-offs are implemented in respective policies.…”
Section: Introductionmentioning
confidence: 99%